SIGLEC1 enables straightforward assessment of type I interferon activity in idiopathic inflammatory myopathies. Issue 1 (17th February 2022) - Graf, Manuel; von Stuckrad, Sae Lim; Uruha, Akinori; Klotsche, Jens; Zorn-Pauly, Lydia; Unterwalder, Nadine; Buttgereit, Thomas; Krusche, Martin; Meisel, Christian; Burmester, Gerd R; Hiepe, Falk; Biesen, Robert; et al.
Abstract : Objective: To evaluate sialic acid binding Ig-like lectin 1 (SIGLEC1) expression on monocytes by flow cytometry as a type I interferon biomarker in idiopathic inflammatory myopathies (IIM). Methods: We performed a retrospective analysis of adult and paediatric patients with the diagnosis of IIM. SIGLEC1 expression was assessed by flow cytometry and was compared with Physician Global Assessment or Childhood Myositis Assessment Scale disease activity scores. Mann Whitney U test and receiver operating characteristic curves were used for cross-sectional data analysis (n=96), two-level mixed-effects linear regression model for longitudinal analyses (n=26, 110 visits). Response to treatment was analysed in 14 patients within 12 months, using Wilcoxon test. SIGLEC1 was compared with interferon-stimulated gene 15/MxA status by immunohistochemical staining of muscle biopsies (n=17). Results: 96 patients with adult (a) and juvenile (j) dermatomyositis (DM, n=38), antisynthetase syndrome (AS, n=19), immune-mediated necrotising myopathy (IMNM, n=8), inclusion body myositis (IBM, n=9) and overlap myositis (n=22) were included. SIGLEC1 distinguished significantly between active and inactive disease with an area under the curve of 0.92 (95% CI 0.83 to 1) in DM and correlated with disease activity longitudinally (aDM: standardised beta=0.54, p<0.001; jDM: standardised beta=−0.70, p<0.001). Response to treatment in DM was associated with a decreasing SIGLEC1 (p<0.01, Wilcoxon test). SIGLEC1 was found upregulated in 8 of 19 patients with AS, 2 of 9 patients with IBM but not in IMNM. Conclusion: SIGLEC1 is a candidate biomarker to assess type I interferon activity in IIM and proved useful for monitoring disease activity and response to treatment in juvenile and adult DM.